Contrasting the 2007 and 2005 Hurricane Seasons: Evidence of Possible Impacts of Saharan Dry Air and Dust on Tropical Cyclone Activity in the Atlantic Basin - Sun, D.; Lau, K. M.; Kafatos, Menas (Chapman University Digital Commons, 2008)
In this study, we provide preliminary evidence of possible modulation by Saharan dust of hurricane genesis and intensification, by contrasting the 2007 and 2005 hurricane seasons. It is found that dust aerosol loadings over the Atlantic Ocean are much higher in 2007 than in 2005. The temperature difference between 2007 and 2005 shows warming in the low-middle troposphere (900–700 hPa) in the dusty region in the eastern North Atlantic, and cooling in the Main Development Region (MDR). The humidity (wind) differences between 2007 and 2005 indicate significant drying (subsidence) in the Western North Atlantic (WNA) in 2007. The drier air in the WNA in 2007 is found to be associated with the further westward transport of the Saharan air layer (SAL). To quantify wind pattern favorable for transport of SAL over the WNA, we define a zonal wind stretch index which shows significant long-term correlation with the mid-level humidity in the WNA. Analyses of the stretch index and related environmental controls suggest that the westward expansion of the Saharan dry air and dust layer can be an important factor in contributing to the difference between the relatively quiescent hurricane season in 2007 and the very active season of 2005.